Geochemical characteristics and significance of the bitumen in Sinian reservoirs in Sichuan basin and its periphery. Issue 1 (November 2020) - Xie, Z Y; Li, J; Zhang, L; Yang, C L; Guo, J Y; Wang, Z H; Li, Z S; Guo, Z Q; Zhang, G W; Li, J; Hao, A S
Abstract: The bitumen of Doushantuo Formation distributed along fractures has been firstly discovered in the dolomite reservoirs of Dou-3 Member in Zigui region, Yichang, Hubei. Research has been conducted using multiple methods on the characteristics of the newly discovered bitumen of Doushantuo Formation, bitumen of Dengying Formation-Longwangmiao Formation in Anyue gas field in Sichuan Basin, and bitumen of Sinian and source rocks of Sinian-Cambrian in Northeast Sichuan. The results show:①The reflectivity of the bitumen of Dou-3 Member is about 2.8%; ② The carbon number of n-alkanes in the bitumen of Dou-3 Member is C13 -C33, where nC17 is the main peak; the relative proportion of the regular steranes is C27 ≈C29 >C28, and C27, C28 and C29 ααα20R steranes are distributed in "L" shape; abundant tricyclic terpanes and pentacyclic triterpanes have been detected, and the abundance of gammacerane is high; Aromatics are mainly phenanthrene series compounds. ③ The heteroatomic compounds in the bitumen of Dou-3 Member are mainly O2 carboxylic acids, and the oxygen compounds in the bitumen of Dengying Formation in Anyue gas field are close to those of the source rocks of Doushantuo Formation. The research results are of vital guiding significance to the study of potential source rocks of Doushantuo Formation in Sichuan Basin and the exploration of oil and gas from the source rocks of Doushantuo Formation.